Alcohol consumption and gastric cancer in Mexico - Lizbeth López-Carrillo; Malaquías López-Cervantes; Armando Ramírez-Espitia; Celina Rueda; Cielo Fernández-Ortega; Sergio Orozco-Rivadeneyra
This paper presents an assessment of alcohol consumption, including the popular Mexican liquor tequila, in relation to the incidence of gastric cancer. We conducted a population-based case-control study in Mexico City, with 220 gastric cancer cases and 752 population-based controls. A food frequency questionnaire was used to measure consumption of alcohol and other dietary items. Grams of ethanol were estimated by the Food Intake Analysis System 3.0 software. After adjustment for known risk factors, wine consumption was positively associated with the risk of developing gastric cancer (OR = 2.93; CI 95% 1.27-6.75) in the highest category of wine consumption, corresponding to at least 10 glasses of wine per month, with a significant trend (p = 0.005). This association remained among intestinal (OR = 2.16; CI 95% 0.68-6.92, p-value for trend = 0.031) and diffuse (OR = 4.48; CI 95% 1.44-13.94, p-value for trend = 0.018) gastric cancer cases. A borderline significant trend between GC risk and total ethanol intake was observed (p = 0.068). Consumption of beer and distilled alcoholic beverages including brandy, rum, and tequila was not associated with GC risk. The results indicate the need to focus on the study of the potential effects of different types of wine, with emphasis on components other than ethanol regarding the incidence of gastric cancer, even among populations with moderate to low levels of alcohol consumption.